Effect of MnO2 doped on physical, structure and optical properties of zinc silicate glasses from waste rice husk ash - Al-Nidawi, Ali Jabar Abed; Matori, Khamirul Amin; Zakaria, Azmi; Mohd Zaid, Mohd Hafiz (Elsevier, 2017)
In this study, an investigation was conducted to explore and synthesize silicate (SiO2) glass from waste rice husk ash (RHA). MnO2 doped zinc silicate glasses with chemical formula [(ZnO)55 + (WRHA)45]100-X[MnO2]X, (where X = 0, 1, 3 and 5 wt%) was prepared by conventional melt quenching technique. The glass samples were characterized using energy dispersive X-ray fluorescence (EDXRF), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Fourier transform infrared (FTIR) spectroscopy, and ultraviolet–visible (UV–Vis) spectroscopy. The results revealed that by increasing the concentration of MnO2, the color of glass samples changed from colorless to brown and the density of glass increased. XRD results showed that a broad halo peak which centered on the low angle (2θ = 30°) indicated the amorphous nature of the glass. FTIR results showed basic structural units of Si-O-Si in non-bridging oxygen, Si-O and Mn-O in the glass network. FESEM result showed a decreasing porosity with an increasing MnO2 content, which was attributed to the Mn ions resort to occupy interstitial sites inside the pores of glass. Besides, the absorption intensity of glass increased and the band gap value decreased with increasing the MnO2 percentage. In this synthesized glass system of MnO2 doped zinc silicate glasses using RHA as a source of silica, the MnO2 affect most of the properties of the glass system under investigation.